2018
DOI: 10.1002/app.46941
|View full text |Cite
|
Sign up to set email alerts
|

Alginate and carboxymethyl cellulose in monolayer and bilayer films as wound dressings: Effect of the polymer ratio

Abstract: In this study, we investigated different proportions of alginate and carboxymethyl cellulose (CMC) biopolymers in the formulation of films to act as wound dressings. With the casting method, monolayer and bilayer (BL) films were produced with alginate/ CMC proportions (weight percentages) of 0:100 (0A), 25:75 (25A), 50:50 (50A), 75:25 (75A), and 100:0 (100A). Thin, homogeneous, and continuous films were obtained with glycerol and crosslinking with CaCl 2 . The fluid uptake, film stability, and morphological, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…However, the peaks attributed to carboxylic groups were shifted from 1660 cm −1 and 1450 cm −1 to 1620 and 1425 cm −1 , indicating the hydrogen bonding interaction between polysaccharides. The shift in the vibrational frequency of hydroxyl groups from 3423 cm −1 (SA) and 3360 cm −1 (AX) to 3350 cm −1 (in films) confirms that hydrogen bonding is present in the films due to the interaction between hydroxyl, carboxylic, and amide groups of AX, SA and GS [ 39 ]. The hydrogen-bonding interactions contribute to increasing the tensile strength of the AXSA films ( Section 3.2.3 ).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…However, the peaks attributed to carboxylic groups were shifted from 1660 cm −1 and 1450 cm −1 to 1620 and 1425 cm −1 , indicating the hydrogen bonding interaction between polysaccharides. The shift in the vibrational frequency of hydroxyl groups from 3423 cm −1 (SA) and 3360 cm −1 (AX) to 3350 cm −1 (in films) confirms that hydrogen bonding is present in the films due to the interaction between hydroxyl, carboxylic, and amide groups of AX, SA and GS [ 39 ]. The hydrogen-bonding interactions contribute to increasing the tensile strength of the AXSA films ( Section 3.2.3 ).…”
Section: Resultsmentioning
confidence: 90%
“…Characteristic bands of the polysaccharide functional groups were present in the spectra of AX and SA ( Figure 3 a). In spectra of both AX and SA, peaks attributed to the –OH, –CH 2 , –COOH, C–O–C (glycosidic linkage), and C–O–H (primary alcohol) are present at around 3650–3300 cm −1 , 2930 cm −1 , 1660 cm −1 , 1450 cm −1 , 1160 cm −1 , and 1055 cm −1 , respectively [ 30 , 39 ]. The spectrum of GS exhibited major transmittance bands of –OH and Amide A (3650–2550 cm −1 ), Amide I (1645 cm −1 ), Amide II (1540 cm −1 ), and C–O–C (1050 cm −1 ) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WVTR for bilayer sponges was calculated as 546.5 ± 120.4 g m −2 while this value was 688.7 ± 135.2 g m −2 for microsphere containing sponges, not significantly different from each other as shown by t ‐test analysis. Both values, however, are lower than WVTR values reported in the literature probably because of the thickness of the sponges which is approximately 1 cm . Previous studies showed that in membrane format, chitosan dressings have WVTR values of 2109–2792 g m −2 , however, this value reduced to 1024–1426 and 839–887 g m −2 for sponge dressings showing that lower transmission rates were obtained when sponges were used instead of thin membranes .…”
Section: Resultsmentioning
confidence: 99%
“…To further enhance the alginate's capacity to heal wounds; in the current research, Carboxymethyl cellulose (CMC) was blended with alginate to produce wound dressings. CMC can maintain a moist environment for wound healing and can absorb large amounts of wound exudates which is particularly favorable in treating diabetic wounds (Li et al 2016;Trevisol et al 2019). Despite showing promising results in previous studies, the proposed wound dressing lacks enough bioactivity for a successful wound healing.…”
Section: Introductionmentioning
confidence: 99%